Penerapan Teknologi Budidaya Ikan dalam Ember (BUDIKDAMBER) Berbasis Internet of Things (IoT) - sabar, sabar; Pertiwi, Kisna; Afriansyah, Aidil; Alfajrin, Achmad Chalid Afif; Mufidah, Zunanik (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service aims to introduce and apply fish farming technology in buckets (BUDIKDAMBER) based on the Internet of Things (IoT) as a learning medium for basic instrumentation control systems. By utilizing IoT technology, this training not only increases efficiency in fish farming, but also provides teachers with a better understanding of basic instrumentation control systems. The results of the analysis have shown that there has been a 24% increase in participants' knowledge in the field of Budikdamber, from 63% to 87%. The aim of implementing this technology certainly indicates an increase in teachers' insight regarding the application of Fish Cultivation technology in buckets based on the internet of things, from those who initially did not understand to understand well